Morphology-controlled solvothermal synthesis of Li2FeSiO4 nanoparticles for Li-ion battery cathodes - Lee, Jeong-Jin; Dinh, Hung-Cuong; Mho, Sun-Il; Yeo, In-Hyeong; Cho, Won Il; Kim, Dong-Wan (ELSEVIER, 2015)
In this work, Li2FeSiO4 nanoparticles with two types of morphologies, spherical and rod-shaped, were prepared via a facile water/ethylene-glycol-based solvothermal method by using different kinds of iron sources and surfactants. When evaluated as a cathode material for lithium-ion batteries, carbon-coated Li2FeSiO4 nanospheres exhibited good cycling stability and large Li storage capacities, delivering 150 and 200 mA h g(-1) at room temperature and 55 degrees C, respectively. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: ELECTROCHEMICAL PERFORMANCE; ELECTRODE MATERIALS; LI2MSIO4 M; CAPACITY; STORAGE; MN; FE